Isolation and development of DNA microsatellite markers for the river catfish (Mystus nemurus) - Hoh, Boon Peng; Siraj, Siti Shapor; Tan, Soon Guan; Yusoff, Khatijah (Asian Fisheries Society, 2007)
The microsatellite markers for Mystus nemurus were isolated using the 5’ anchored PCR procedure. A degenerate primer was designed for the construction of the genomic library. Fourteen clones were sequenced and revealed a total of 45 microsatellite repeats. From these, 20 specific primer pairs were designed and employed to characterize unrelated fishes from six populations of M. nemurus. Thirteen loci were found to be polymorphic. The allelic frequencies ranged from 0.007 to 0.800, while the levels of heterozygosity ranged from 0.0563 (MnBp5-1-115b) to 0.8714 (MnBp5-1-12a).